The Centennial Celebration of the Battle of Lundy’s Lane and of One Hundred Years of Peace - Young, Elaine (Ontario History, 2012)
This article examines the centenary celebration of the Battle of Lundy’s Lane, held under the auspices of the Lundy’s Lane Historical Society on 25 July 1914. At this time Canada was attempting to define its place in the world, and was coming to terms with a growing Anglo-American rapprochement. At the prodding of Canadian federal bodies, what had originally been intended as a Canadian celebration was transformed into an international one involving Canadian, and American representatives. In this way the celebration of the anniversary of the Battle of Lundy’s Lane was combined with that of one hundred years of peace between Britain and the United States. The resulting ceremony was filled with conflicting messages about Canada’s history and its relationship with its southern neighbour as participants tried to balance Canada’s attachment to the empire and its growing closeness with the United States, while commemorating the last great battle between them.